2018
DOI: 10.1002/bjs.10950
|View full text |Cite
|
Sign up to set email alerts
|

Timing of carotid intervention

Abstract: Flimsy evidence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In fact, the mean delay in all RCTs was over 14 days and even over 1 month in all RCTs except two. 89 The lack of robust data investigating the safety and efficacy of CAS in the acute/peri-stroke period is particularly significant given the routine use of ECR for stroke.…”
Section: Acute Stroke and Tandem Lesionsmentioning
confidence: 99%
“…In fact, the mean delay in all RCTs was over 14 days and even over 1 month in all RCTs except two. 89 The lack of robust data investigating the safety and efficacy of CAS in the acute/peri-stroke period is particularly significant given the routine use of ECR for stroke.…”
Section: Acute Stroke and Tandem Lesionsmentioning
confidence: 99%
“…3 As a result of this initially high recurrence risk, international guidelines recommend performing carotid revascularisation within 14 days of the first event. 4 In practice, this guideline is often not met, 5 although earlier CEA reduces the recurrent ischaemic event rate. 6 Therefore in recent years, multiple studies have investigated factors associated with this delay.…”
Section: Introductionmentioning
confidence: 99%
“…In light of evidence suggesting that very urgent intervention may increase procedural risk due to presumed plaque vulnerability, procedural timing has to be planned more carefully. 37,38 In previous studies the advantage of CEA over CAS with respect to prevention of new DWI lesions has already been demonstrated. 2,3 Although a meta-analysis of European RCT data showed that CAS was associated with a significantly higher risk of procedural death/stroke risk after 30 days than CEA, follow up results of these RCTs show that CAS appears to be as durable as CEA after the first 30 days.…”
Section: Discussionmentioning
confidence: 95%
“…35,36,41 Another topic of interest is procedural timing in symptomatic patients. 37 As cerebrovascular events are more likely to occur in patients with unstable plaque, one could rationalise that timing of the procedure in symptomatic patients may influence the chance of dislodgement of plaque debris and therefore new DWI lesions, in line with research suggesting increased stroke risk after very urgent CEA. 38 Future research on intervention timing should incorporate presence of DWI lesions as one of the secondary outcome measures.…”
Section: Discussionmentioning
confidence: 99%